Características dos frutos de cultivares de pessegueiros e nectarineira, no município de Botucatu – SP - Ramos, Dayana Portes [UNESP]; Leonel, Sarita [UNESP] (Universidade Federal de Uberlândia (UFU), 2008)
The research had as purpose to evaluate the fruits physical-chemical characteristics of peach cultivars (CP-9553 CYN, CP951 C, Tropic Beauty, Cascata 953, Cascata 797, Cascata 587, Precocinho, Conserva 693, Diamante Mejorado, Turmalina e Marli and Sun Blaze nectarine at Botucatu, São Paulo, Brazil region. It were evaluated the fruits fresh matter, longitudinal and transversal diameters, and the crop period. In relation the physical-chemical characteristics of fruits, it was evaluated the texture, the pH, tritatable acid and soluble solids. The results showed significant differences between the cultivars where the fruits fresh matter were 68,6g ('CP-9553 CYN') and 141,35g ('Cascata 953'); the fruits longitudinal diameter were 50,32mm ('Marli') and 72,12mm ('Conserva 693') and the fruits transversal diameter were 50,50mm ('CP-9553 CYN') and 62,90mm ('Cascata 953'). The post-harvest characteristics also had significant differences. The texture had changes at 517,00gf ('Marli') and 168,47gf ('Precocinho'); the soluble solids were 9,73 degrees Brix on Marli cultivar. The pH was about 3,36 on 'Diamante Mejorado' until 4,48 on CP-9553 CYN cultivar and the acidity was 0,96g of citric acid 100g(-1) fruits juice on Tropic Beauty cultivar. The crop period of the cultivars evaluated were the end of September month until 15(th) November month, being the earliest cultivars Tropic Beauty, CP-951 and CP-951 CYN and the latest cultivar were Marli. It was observed that the news cultivars, until in observations, with Cascata 953, Cascata 797 and Cascata 587, showed crops potential at Botucatu/SP region.

O objetivo do trabalho foi avaliar características de tamanho e qualidade dos frutos de pessegueiros ‘CP-9553 CYN’, ‘CP-951 C’, ‘Tropic Beauty’, ‘Cascata 953’, ‘Cascata 797’, ‘Cascata 587’, ‘Precocinho’, ‘Conserva 693’, ‘Diamante Mejorado’, ‘Turmalina’ e ‘Marli’, e da nectarineira ‘Sun Blaze’, no município de Botucatu/SP. Foram mensurados o diâmetro, peso e altura média dos frutos, bem como a época de maturação. Também foram avaliados atributos físico-químicos dos frutos, por meio das análises de textura, pH, acidez titulável e sólidos solúveis. Os resultados obtidos demonstraram algumas variações significativas entre os cultivares, na qual o peso dos frutos variou de 68,64 (‘CP-9553 CYN’) a 141,35g (‘Cascata 953’); a altura de 50,32 (‘Marli’) a 72,12 mm (‘Conserva 693’) e o diâmetro de 50,50 (‘CP-9553 CYN’) a 62,90 mm (‘Cascata 953’). Também houve diferenças significativas entre os cultivares com relação à textura que variou de 517,00 (‘Marli’) a 168,47 gf (‘Precocinho’); o teor de sólidos solúveis variou de 9,73 (‘CP-951 C’) a 16,30 º Brix (‘Marli’); o pH de 3,36 (‘Diamante Mejorado’) a 4,48 (‘CP-9553 CYN’) e a acidez de 0,32 (‘Cascata 587’) a 0,96g de ácido cítrico.100g-1de polpa (‘Tropic Beauty’). O período de colheita dos diferentes cultivares variou do final do mês de setembro até meados de novembro, sendo que os cultivares Tropic Beaty, CP-951 C e CP-951 CYN foram os mais precoces e ‘Marli’ o mais tardio.
Fruits characteristics of peach and nectarine cultivars with crop potential at Botucatu region
Keywords: Prunus persica; Peach; Nectarine; Cultivars; Post-harvest; Agronomic characteristics